The Influence of Promotion, Price, and Product Quality of Fresh Fruit Through the JSM Bazaar Program on Purchasing Decisions at Indomaret Fresh Malang - Fatoni, Ahmad (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives:This study aims to analyze the influence of promotion, price, and product quality—both partially and simultaneously—on purchasing decisions for fresh fruit at Indomaret Fresh Malang through its JSM (Friday, Saturday, Sunday) Bazaar program. Background Problems: There is significant uncertainty regarding which specific marketing factors—promotion, price, or product quality—most critically influence purchasing decisions for fresh fruit within the unique context of a time-limited promotional program (JSM Bazaar) in a modern retail setting. Although promotional strategies like the JSM Bazaar attract attention, consumer decisions are complex and not driven by promotion alone Novelty: The research provides a specific contextual contribution by examining the unique marketing strategy of the JSM Bazaar in a modern retail setting for fresh fruit products—a segment less explored compared to studies on durable goods or services. Research Methods: This research employs a quantitative approach with a survey method. The population comprises Indomaret Fresh Malang consumers who purchased fresh fruit at the JSM Bazaar. A sample of 96 respondents was determined using the Cochran formula and simple random sampling. Data were collected via a 4-point Likert scale questionnaire and analyzed using multiple linear regression analysis with SPSS. Finding/Results: Promotion, price, and product quality each have a positive and significant partial effect on purchasing decisions. Simultaneously, these three variables have a significant positive effect on purchasing decisions.Product quality emerges as the most dominant influencing factor. Conclusion: The findings offer practical strategic recommendations for Indomaret Fresh to optimize its marketing mix, emphasizing the critical role of product quality alongside promotion and pricing within the JSM Bazaar framework.